2016
DOI: 10.1186/s12864-016-3190-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental transcriptome of resting cell formation in Mycobacterium smegmatis

Abstract: BackgroundMycobacteria, along with exospore forming Streptomyces, belong to the phylum actinobacteria. Mycobacteria are generally believed to be non-differentiating. Recently however, we showed that the mycobacterial model organism M. smegmatis is capable of forming different types of morphologically distinct resting cells. When subjected to starvation conditions, cells of M. smegmatis exit from the canonical cell division cycle, segregate and compact their chromosomes, and become septated and multi-nucleoided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…In mc 2 155, Shell et al ( 2015 ) revealed a high abundance of leaderless mRNAs and small proteins by the combination of RNA-seq and ribosome profiling data. Other studies mainly focused on the identification of DEGs in different conditions (Petridis et al, 2015 ; Li et al, 2016 ; Wu et al, 2016 ; Hillion et al, 2017 ). However, no comprehensive insights have been achieved regarding M. smegmatis yet.…”
Section: Introductionmentioning
confidence: 99%
“…In mc 2 155, Shell et al ( 2015 ) revealed a high abundance of leaderless mRNAs and small proteins by the combination of RNA-seq and ribosome profiling data. Other studies mainly focused on the identification of DEGs in different conditions (Petridis et al, 2015 ; Li et al, 2016 ; Wu et al, 2016 ; Hillion et al, 2017 ). However, no comprehensive insights have been achieved regarding M. smegmatis yet.…”
Section: Introductionmentioning
confidence: 99%
“…For mycobacteria treated with antibiotics, which disrupt formation of the cell wall (such as Cycloserine, ethambutol, and isoniazid), elevated transcription of the transcriptional regulator whiB2 was shown [ 38 , 39 ]. Mycobacterium smegmatis also overexpresses whiB2 during the transition to uncultivated forms [ 40 ]. In our study, we detected the increased expression of MSMEG_1831/whiB2 upon Olivomycin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Ftsw , ftsz , and pbp3 -encoded proteins can form a ternary complex to potentially regulate peptidoglycan biogenesis. Roda glycosyltransferase is also involved in peptidoglycan synthesis ( Wu et al, 2016 ). Figure 6C shows that Subnet 2 contains 13 ESX-1 secretory system-related genes.…”
Section: Resultsmentioning
confidence: 99%